Essential Oil and Its Antimicrobial Activity from Ethiopian Acokanthera schimperia - Matebie, Wondwosen A; Zhang, Wanchang; Zhang, Shuo; Xie, Guangbo (Edelweiss Applied Science and Technology, 2019)
Background: Acokanthera schimperia is a medicinal plant, which has been used by traditional healers as a curing agent in Ethiopia. Objective: The constituents of the essential oil, which was extracted from the leaves of A. schimperia, were investigated, and its antibacterial and antifungal activities were studied. Materials and Methods: The essential oil was extracted by an ordinary steam distillation process, and its chemical constituents were analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). Antibacterial and antifungal activities of the oil were studied by micro-dilution method against Escherichia coli, Bacillus subtilis (for bacteria), and Candida albicans (for fungus) respectively. Result: From the essential oil, 21 compounds were recognized, and making up 56.06 %. However, the essential oil doesn’t show any antimicrobial activities. Conclusion: This is the first research on A. schimperia concerning its essential oil and antimicrobial activities.